1901 Fla. Laws 262 - (:unkn) unknown (My University, 1901)
§ 33: That the Council shall have power . . . to regulate or suppress the sale and use of fire-crackers and all other fire-works, toy pistols, air-guns and sling shots; to regulate the storage of gunpowder, tar, pitch, rosin, saltpetre, gun-cotton, coal-oil and all other combustibles, explosives and inflammable material
Keywords: GUNPOWDER - STORAGE; TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES